2019
DOI: 10.1007/s11606-019-05342-7
|View full text |Cite
|
Sign up to set email alerts
|

Military Sexual Trauma in Older Women Veterans: Prevalence and Comorbidities

Abstract: BACKGROUND: Recent attention has highlighted the common occurrence and health consequences of military sexual trauma (MST) in younger women veterans. However, almost nothing is known about MST in older veterans. OBJECTIVE: To describe MST among older women veterans, including prevalence and common comorbidities. DESIGN: Cross-sectional observational study, using data from national Department of Veterans Affairs medical records. PARTICIPANTS: Population-based sample of women Veterans aged 55+ with at least one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 53 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…A limited number of previous studies have examined these traumas in relationship to hypertension using cross‐sectional designs. 7 , 8 , 31 , 32 , 33 , 34 , 35 As hypertension is a major risk factor for CVD 53 , 54 the present findings highlight the importance of considering these measures of sexual violence for women’s cardiovascular health.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A limited number of previous studies have examined these traumas in relationship to hypertension using cross‐sectional designs. 7 , 8 , 31 , 32 , 33 , 34 , 35 As hypertension is a major risk factor for CVD 53 , 54 the present findings highlight the importance of considering these measures of sexual violence for women’s cardiovascular health.…”
Section: Discussionmentioning
confidence: 70%
“… 7 , 8 , 31 , 32 These studies did not investigate potential joint effects of sexual assault and workplace sexual harassment and used cross‐sectional designs, with many studies also using samples of female veterans. 7 , 8 , 31 , 32 , 33 , 34 , 35 , 36 Another limitation of these prior studies is that they did not account for other traumatic experiences in the absence of sexual violence, such as accidents, disasters, or unexpected death of a loved one, that are also common and have been linked to adverse mental and physical health. 37 , 38 , 39 , 40 …”
mentioning
confidence: 99%
“…Notably, sexual violence is highly prevalent in the United States (US), with 44% of women having experienced sexual assault in their lifetime (Smith et al, 2018). A limited literature has linked sexual assault to cerebrovascular health, with one study nding a history of sexual assault was associated with increased risk of self-reported stroke (Santaularia et al, 2014), and another nding military sexual assault (sexual assault or repeated, threatening sexual harassment in the context of military service) linked to medical record-documented cerebrovascular disease (Gibson et al, 2020). However, no prior literature has examined sexual assault in relation to WMHs.…”
Section: Discussionmentioning
confidence: 99%
“…2 MST experiences are associated with increased risks for chronic conditions and mental health conditions, with posttraumatic stress disorder (PTSD) and depression among the most frequent mental health consequences of MST. 3,4 To promote access to care for MST-related conditions, the VHA has implemented universal screening for MST and provides care for related conditions without co-pay. VHA surveillance data for fiscal year 2020 indicate that 63.4% of women and 53.6% of men with newly detected MST accessed mental health care related to the MST.…”
Section: Introductionmentioning
confidence: 99%